Peningkatan Pengetahuan dan Keterampilan Ibu Nelayan Desa Tanjung Tiram Melalui Program Kemitraan Masyarakat (PKM) Pengolahan Ikan - Huli, La Ode; Hazairin Nadia, Laode Muhamad; Piliana, Wa Ode; Sitti Zubaydah, Wa Ode; Nyoman, Desak; Novita, Dian; Assidik, Fajrin (Vokasi Universitas Halu Oleo, 2020)
Tanjung Tiram is a coastal village whose residents mainly works as fishermen and many benefits from its coastal to search for fish and fulfill their daily needs. A Community Service Program through Community Partnership was conducted for 2 days from 27-28 October 2019 in Tanjung Tiram, North Moramo District, South Konawe Regency, Southeast Sulawesi Province. The objective of the program was to improve the knowledge and skills of society living in the village through the production of fish base processing products. The program was carried out by training the society creating fish base products and as an alternative income for the fishermen family. The targets of the program were women and mother household. The output achieved out of this program was the ability of society to understand and know how to create fish base processing products particularly meatball and fish nuggets that have never been made before.